Spectral energy distribution analysis of class i and class ii fu orionis stars - Gramajo, Luciana Veronica (2014)
FU Orionis stars (FUors) are eruptive pre-main sequence objects thought to represent quasi-periodic or recurring stages of enhanced accretion during the low-mass star-forming process. We characterize the sample of known and candidate FUors in a homogeneous and consistent way, deriving stellar and circumstellar parameters for each object. We emphasize the analysis in those parameters that are supposed to vary during the FUor stage. We modeled the spectral energy distributions of 24 of the 26 currently known FUors, using the radiative transfer code of Whitney et al. We compare our models with those obtained by Robitaille et al. for Taurus class II and I sources in quiescence periods by calculating the cumulative distribution of the different parameters. FUors have more massive disks: we find that ~80% of the disks in FUors are more massive than any Taurus class II and I sources in the sample. Median values for the disk mass accretion rates are ~10–7 M ☉ yr–1 versus ~10–5 M ☉ yr–1 for standard young stellar objects (YSOs) and FUors, respectively. While the distributions of envelope mass accretion rates for class I FUors and standard class I objects are similar, FUors, on average, have higher envelope mass accretion rates than standard class II and class I sources. Most FUors (~70%) have envelope mass accretion rates above 10–7 M ☉ yr–1. In contrast, 60% of the classical YSO sample has an accretion rate below this value. Our results support the current scenario in which changes experimented by the circumstellar disk explain the observed properties of these stars. However, the increase in the disk mass accretion rate is smaller than theoretically predicted, although in good agreement with previous determinations.